A dissolution and reaction modeling for hydrolysis of TEOS in heterogeneous TEOS-water-HCl mixtures under ultrasound stimulation - Donatti, D. A.; Ruiz, A. I.; Vollet, D. R. (Elsevier B.V., 2002)
A simplified dissolution and reaction modeling was employed to study the hydrolysis of heterogeneous tetraethoxysilane (TEOS)-water-HCl mixtures under ultrasound stimulation. The nominal pH was changed from 0.8 to 2.0. The acid specific hydrolysis rate constant was determined as k = 6.1 mol(-1) 1 min(-1) [H+](-1) at 39 degreesC, in good agreement with the literature. Along the heterogeneous step of the reaction, the ultrasound maintains an additional quantity of water under a virtual state of dissolution besides the water dissolved due to the homogenizing effect of the alcohol produced in the reaction. The forced virtually dissolved water is probably represented by water at the TEOS-water interface during the heterogeneous step of the reaction. The mean radius of the heterogeneity represented by water dispersed in TEOS phase, while hydrolysis has not started yet, was evaluated as about 290 A. The HCl concentration accordingly increases the hydrolysis rate constant but its fundamental role on the immiscibility gap of the TEOS-water-ethanol system has not been unequivocally established. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: tetraethoxysilane; sono-hydrolysis; sol-gel